PREDICTION OF MADECASSOSIDE (CENTELLA ASIATIACA) AFFINITY AS ANTIPARKINSON DRUG ON DOPAMINE RECEPTOR D1: MOLECULAR DOCKING ANALYSIS - Shinta Kusumawati; Khotimah, Husnul; Endharti, Agustina Tri; Balafif, Farhad; Zakiyah, Rima (MNJ (Malang Neurology Journal), 2025)
Background: Parkinson's disease results from the gradual degeneration of dopamine neurons in the brain's substantia nigra pars compacta. The Dopamin receptor D1 (DRD1), which controls nerve growth and behavior, is the most prevalent dopamine receptor in the human nervous system. Objective: To determine the affinity of madecassoside on dopamine D1 receptors as a potential for anti-Parkinson's medications. Methods: The RSCB PDB database provided the chosen target protein's three-dimensional structure. namely DRD1. The PubChem database provided the 3D structure of the Madecassoside sample (CID: 45356919) and the PDB ligand control Rotigotine (CID: 59227). Autodock Vina, which was integrated with Pyrx v.1, was used for docking. Results: The madecassoside has a lower binding energy than the PDB control in the form of Rotigotine. The docking results showed that  madecassoside compounds formed more hydrogen bonds than Rotigotine. It was predicted that madecassoside and the dopamin receptor 1 receptor would create a stability complex. Conclusion: Madecassoside was predicted create a stability complex with DRD1.